TECHNOCRATIC DISCOURSE AS AN ARTICULATION OF STRUCTURAL CONTRADICTIONS OF TECHNOGENIC CIVILIZATION - Abysova, Mariia; Honcharenko, Kateryna; Lovkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
In contemporary technogenic society, social processes are increasingly interpreted and justified as technical problems requiring optimization and control. This shift is accompanied by the growing role of expert knowledge and infrastructural coordination in decision-making, which transforms the forms of public legitimation of governance. The aim and tasks. The aim of the study is to conceptualize technocratic discourse and to clarify its role in articulating the structural contradictions of technogenic civilization. The tasks include analyzing the methodological potential of Habermas’s theory of rationality, identifying key contradictions of technogenic development, and describing discursive strategies of legitimation. Research methods. The study is based on Habermas’s distinction between instrumental and strategic rationality, supplemented by approaches from philosophy of technology and STS. A discourse-analytical perspective is applied to examine practices of public justification. Research results. Technocratic discourse is defined as a set of communicative practices in which social processes are interpreted through technical necessity, efficiency, and controllability, while decisions are presented as functionally justified and practically non-alternative. It is shown that such discourse emerges in the context of complex socio-technical systems and the growing role of technocratic forms of justification in governance. Key strategies include appeals to expert knowledge, the rhetoric of efficiency, and the framing of decisions as inevitable. Discussion. The findings are interpreted in relation to Habermas’s theory of system and lifeworld, as well as broader approaches to discourse and power. Technocratic discourse is understood as a mechanism that transforms normative conflicts into technical and managerial problems. Conclusions. Technocratic discourse functions both as a form of representation and as a mechanism of reduction, through which the structural contradictions of technogenic civilization are translated into technical and managerial terms, limiting the visibility of normative alternatives.